Encapsulation of tamoxifen and magnetic nanoparticles in poly lactic acid using supercritical antisolvent process - Alias, Dalila (2020)
Drug encapsulation offers advantages in controlled drug release and targeted drug delivery applications. Limited work had been carried out to encapsulate drug, magnetic nanoparticles and polymer in a single step process. The supercritical antisolvent (SAS) process offers a single step precipitation process and operates at a low temperature. Therefore, the SAS process has potential to encapsulate drug, polymer and magnetic nanoparticles. This study aims to use the SAS process to encapsulate tamoxifen (TAM) within a biodegradable polymer, Poly-L-Lactic acid (PLLA) for controlled drug delivery applications and later incorporated magnetic nanoparticles for targeted drug delivery applications. The investigation began with manipulating operating pressure, the concentration of polymer, solution flow rate, and temperature of the system of the SAS system. The operating conditions affect the particle size and morphology of the encapsulated particles. The particle size of TAM-PLLA particles was successfully reduced from 1.85±0.06 μm to 0.43±0.03 μm with low particles agglomeration. The target particle size is below 1 μm to cater to the need to cross the tumor vasculature and to provide a stable colloidal system, which was covered in the later part of this study. TAM-PLLA particles have shown controlled release behavior by diffusion mechanism. In the second stage of this study, the potential of the SAS process in developing drug-magnetic nanoparticles particles in polymer for targeted drug delivery was assessed. Tamoxifen was encapsulated with oleic acid magnetic nanoparticles (OAMNP) in poly-l-lactic acid. Introducing OAMNP in the formulation increases the complexity of the SAS process, as the quinary system is involved; rather than a typical quaternary system. This work has identified the method to incorporate OAMNP in sample preparation to ensure the success of the SAS process and maintaining the magnetization characteristics of OAMNP in the final product. Polymer and OAMNP concentrations were manipulated to obtain the smallest particle size with non-agglomerated morphology and acceptable saturation magnetization value. Under the optimum encapsulation conditions, 43% of drug loading with a size of 0.67±0.09 μm and non-agglomerated particles. The superparamagnetic behaviour of formed particles with a saturation magnetization value of 4.1337 emu/g is achieved. These results are encouraging for tamoxifen controlled and targeted delivery applications. The stability of particles in the biological environment was assessed in the colloidal stability study. Encapsulated particles were dispersed in various biological media such as Phosphate Buffered Solution (PBS), culture media, and culture media with serum. Factors such as concentration, time, and temperature were varied, and samples were evaluated based on particle size and zeta potential value. The condition that gives the most stable colloidal stability was identified. Our final interest is to study the cytotoxicity of the final products in comparison to raw material. Brine shrimp assay was proposed as a mechanism to evaluate the cytotoxicity of TAM-OAMNP-PLLA. Lethal concentration LC50 was the concentration required to kill 50% of the sample population and has been used as a guideline to determine the toxicity of a sample. It was found that encapsulated tamoxifen (with and without) magnetic nanoparticles was non-toxic compared to raw tamoxifen, which possessed LC50 of 0.38 mg/mL as compared to 1.51 mg/mL (tamoxifen with PLLA) and 1.09 mg/mL (tamoxifen, magnetic nanoparticles with PLLA). Overall, the SAS process has successfully produced encapsulated tamoxifen in Poly-l-lactic acid and tamoxifen with magnetic nanoparticles in Poly-l-lactic acid with particle size less than 1 μm and spherical morphology. The final products from the SAS process have proven to have potential in controlled and targeted drug delivery applications.